Deposition of hydroxyapatite coatings by axial plasma spraying: Influence of feedstock characteristics on coating microstructure, phase content and mechanical properties - Ganvir Ashish; Markocsan Nicolaie; Balani Kantesh; Nagar Sainyam (ELSEVIER SCI LTD, 2022)
Axial plasma spray is one of the thermal spray techniques to deposit multifunctional advanced coatings. The present work explores the use of this process to deposit thin, continuous, and adherent Ca5 (PO4)3OH (hydroxyapatite, HAp) coatings and characterize its microstructure, phases, hardness and adhesion strength. Three different suspension-deposited HAp coatings were investigated and compared with powder-deposited HAp coating on a Ti6Al4V substrate. The effect of mean solute particle size and solid-loading in the suspension has been explored on the evolution of microstructure, phase content and mechanical properties of axial suspension plasma sprayed (ASPS) coatings. Phase-characterization has shown retention of hydroxyapatite phase and coating crystallinity in the deposited coatings, whereas the adhesion strength of the HAp coating decreased from -40 MPa to -13 MPa when bioglass was added to the feedstock material. The lower solid load content and lower mean solute particle size in the suspension were found to be beneficial in achieving porous, rougher, and welladhering coatings. This work concludes that ASPS can potentially deposit thin HAp coatings (< 50 ?m) with high adhesion strength.